Analiza językowa sloganów reklamowych związanych z branżą kosmetyczną - Gieda, Joanna (Kultury Wschodniosłowiańskie – Oblicza i Dialog, 2018)
In the modern world it can be easy to encounter advertising slogans that are supposed to grab the attention of a potential recipient as well as affect their imagination and sensitivity. This communication tends to convince the client that buying the advertised product would make them feel exceptional. This article focuses on linguistic gimmicks that are used by marketing experts in order to convince the client to a certain product. The analysis in based on the cosmetics sector. The lexical database consists of websites, television commercials and Internet advertisements.